2008
DOI: 10.3171/foc/2008/25/8/e17
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous iliac screw placement: description of a new minimally invasive technique

Abstract: Minimally invasive spinal instrumentation techniques have evolved tremendously over the past decade. Although there have been numerous reports of lumbar instrumentation performed via a percutaneous or minimal incisional route, to date there have been no reports of minimally invasive iliac screw placement. A method was developed for accurate placement of minimally invasive iliac screw placement based on a modification of currently available percutaneous lumbar instrumentation techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 23 publications
1
19
0
1
Order By: Relevance
“…Multiple studies have shown that long instrumentation to the sacrum without supplemental pelvic fixation predisposes to implant failure [17][18][19]. Methods of fixation to achieve effective iliac fixation have evolved over from Galveston technique to iliac screws in recent decades.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that long instrumentation to the sacrum without supplemental pelvic fixation predisposes to implant failure [17][18][19]. Methods of fixation to achieve effective iliac fixation have evolved over from Galveston technique to iliac screws in recent decades.…”
Section: Discussionmentioning
confidence: 99%
“…The potential upside of dual screw fixation would be greater biomechanical strength with decreased instrumentation-related postoperative complications such as screw pullout, pseudarthrosis, and sacral insufficiency fracture. 16,17 The potential downside of a second screw is added muscle and fascia dissection, increased postoperative pain, problems with sexual function, 2,4 increased cost, and possibly increased infection risk due to the added exposure and hardware.…”
Section: Discussionmentioning
confidence: 99%
“…Iliac screws are placed using the obturator outlet view for percutaneous cannulation as previously described. 19 For iliac screws a window is made in the posterior superior iliac spine to avoid screw head prominence. Each needle is then exchanged for a K wire.…”
Section: Surgical Techniquementioning
confidence: 99%